GENERALIZED B-STRONGLY B*-SEPARATION AXIOMS IN TOPOLOGICAL SPACES. - P.Selvan; M.J.Jeyanthi (International Journal of Research Science and Management, 2017)
The purpose of this paper is to introduce a new class of spaces via gbsb*-open sets and gbsb*-difference sets. Further we give some basic properties and their various characterizations Mathematics Subject classification 2010: 54A05